Penerapan Metode RUP dalam Pengembangan Sistem Informasi Kepegawaian PT Navia Persada Abadi - Ferdiansyah, Muhammad; Mardiani, Mardiani (Universitas Multi Data Palembang, 2025)
PT Navia Persada Abadi operates in the field of fuel oil distribution and transportation services, facing obstacles in managing personnel data which is still manual, such as absenteeism recaps, leave applications and recruitment. This leads to processes that are inefficient and prone to errors. To overcome this problem, a web-based personnel information system was designed using the Rational Unified Process (RUP) method. This system includes features for managing employee data, attendance, recruitment, leave, reward & punishment, promotion and demotion. The implementation of a PHP and MySQL based system is expected to increase efficiency, accuracy and transparency in personnel management in the company. With this system, PT Navia Persada Abadi can increase operational productivity and provide better service to employees.